Re-examining Affordances, technical agency, and the politics of technologies of cultural production - Srauy, Sam; Neff, Gina; Coleman, Miles; Beyer, Jessica; McVeigh-Schultz, Joshua (AoIR Selected Papers of Internet Research, 2013)
The panel’s theme centers on the concept of affordances. Collectively, the panel’s papers seek to make the idea of affordances more concrete by critically evaluating some taken for granted aspects of affordances in Internet research. Originally proposed by psychologist James Gibson, affordance is a theoretical framework which seeks to illuminate how human beings’ cultural environment inform their understanding of objects’ physical features. As it was original imagined by Gibson, aspects of the physical world illicit cues of how they may be used. However, which cues are put into practice is determined by the social world of humans. From its original deployment by Gibson, the concept of affordances has been widely used in the fields such as communication, sociology, science and technology studies, and human computer interaction. This panel builds on the work from a previous panel. Last year at AoIR 13, some members of Culture Digitally, a research community, organized and presented research that addressed the concept of affordances. After engaging with the concept of affordances through empirical work, each member of the panel individually engaged critically with the theoretical concept. This proposed panel is a continuation of that conversation. Some of the panel members are new and some have returned. The first paper argues that in many cases the affordances of an online space have a crucial role in creating the “shape” of an online community including the adoption of cultural norms based on the structural restrictions of a given space. What then becomes a driving factor in producing outcomes—the structure of a technological space, the guiding principle of a cultural value, or the agency of actors? Anonymity in online communities offers a useful lens to explore questions about affordances and online communities, in particular, in relation to political mobilization. This paper is an attempt to articulate how the intricacies of anonymity can generate different types of political outcomes. The second paper argues that the best way to understand how affordances shape scholars’ understanding “determinism” is to reformulate the idea that technology and human sociality constitute an interplay. Contrary to the idea that this interplay is symmetrical, however, the authors argues that this interplay is best understood as inherently asymmetrical. Using the metaphor of a virus, the authors question whether the “agency” of technology necessarily needs to imply the same kind of agency that human actors imply. The third paper further analyzes the interplay between technological and social agency by arguing that social agency must have more of an impact on how these affordances ought to be understood. This essay rereads selected research from the 1990s in order to draw attention to the ways that users can act like designers—manipulating ‘space’ with an eye towards reshaping ‘place.’ Extrapolating to contemporary online contexts, we can similarly identify users’ own reflexive attention to affordance as increasingly key to understanding the entanglement of technical systems and social practice. Citing examples such as “retweets”, the author argues that technical agency exists only in the presence of social collaboration (i.e., social agency). The final paper examines the theoretical implications of the concept of affordances. Without taking a firm stance one way or another, the author argues that the continuous shift away from Gibson’s conception of the term warrants a reconsideration of the theory. Employing a Foucauldian lens, the author reexamines what have been understood as affordances as articulations of power relations in human society. Following this line of reasoning and situating itself with other papers in this panel (and especially the second), the author asks whether or not social agency ought to be given more consideration if we do assume affordances exist. By contrasting the theory of affordances with other competing theories, the author unpacks these implications, readdresses earlier critiques of affordances, and offer a potential alternative that might prove useful.